Comércio eletrônico e a influência no comportamento consumidor no turismo - Alves Júnior, Carlos Castro (2015)
The purpose of this project is to expose a new benchmark business model, that has grown significantly in the tourism sector, modality that has the internet as a means of dissemination, communication, negotiation, and mainly effect the purchase of the tourism product. This model is called the Virtual Market or Electronic Commerce. Still can not scale up to where the internet can reach and influence in people's lives, but it is possible to establish clear and tangible examples that both, the routine as consumer behaviour have changed significantly in such a short time. A long time the technology is no longer a tool experience in laboratories, to become part of modern man's daily life, and this inevitable reality has caused many changes in people's lives. Therefore, it becomes a personal habits rehabilitation process, consumption practices, even structural reconstruction in some market segments, such as tourism. Here, tourism is considered not only as a business segment belonging to the tertiary sector, but as an economic activity of relevance in the production chain for regional development. The impact of changes are seen in consumer behaviour, both in the research process, decision making and execution of the purchase, as well as the new customer-supplier relationship, and billing results.